Nugget Gemarikan (Steamed Rice Mixed with Additional of Mackerel) as an Alternative Food to Prevent Stunting - Candradewi, Anak Agung Istri; Ipa, Agustian; Asikin, Hijrah (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Stunting remains a crucial public health issue in Indonesia. This condition of impaired growth is primarily triggered by chronic malnutrition, especially during the first 1,000 days of life (HPK). The impacts of stunting are irreversible on children's growth and cognitive development. Although the prevalence of stunting in Indonesia decreased to 21.6% in 2022, this figure is still far from the national target of 14% by 2024. One of the strategies to address stunting is through the provision of protein- rich supplementary foods, such as mackerel. This study aimed to design and modify a functional food product named "Nugget Gemarikan". The method employed was an experimental study with a randomized block design, involving four treatment levels of mackerel addition: P1 (0%), P2 (16.7%), P3 (33.3%), and P4 (50%). Organoleptic testing was conducted by 30 trained panelists to assess subjective quality (taste, color, aroma, and texture) using hedonic and numeric tests. The data were then analyzed using ANOVA. The results showed that Nugget Gemarikan with 50% mackerel addition (P4) had the highest nutritional value, specifically 349.4 kcal of energy and 14.3 grams of protein per serving. Nevertheless, panelists overall preferred the formulation with 33.3% mackerel addition (P3). ANOVA testing revealed a significant difference in taste, texture, and aroma across treatments (p-value < 0.05), except for the color aspect (p-value > 0.05). This Nugget Gemarikan has the potential to be a balanced, nutritious supplementary food that helps meet the daily needs of toddlers and prevent stunting.